Preliminary Findings of mRNA COVID-19 Vaccine Safety in Pregnant Persons. Issue 12 (December 2021) - Shimabukuro, Tom T.; Kim, Shin Y.; Myers, Tanya R.; Moro, Pedro L.; Oduyebo, Titilope; Panagiotakopoulos, Lakshmi; Marquez, Paige L.; Olson, Christine K.; Liu, Ruiling; Chang, Karen T.; Ellington, Sascha R.; Burkel, Veronica K.; et al.
Abstract : (Abstracted from N Engl J Med 2021;384:2273–2282) The first coronavirus disease (COVID-19) vaccines in the United States were the messenger RNA (mRNA) vaccines BNT162b2 (Pfizer-BioNTech) and mRNA-1273 (Moderna). Pregnant persons were excluded from the original Emergency Use Authorization (EUA) issued by the Federal Drug Administration (FDA) in December 2020.